Role of Ethnicity and Environment as Risk Factors on Asthma in Two Ethnic Groups in Michigan State, United States of America - Jamil, Hikmet; Dafdony, Isam; Yasso, Fady; Lami, Faris; Arnetz, Bengt B. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Asthma is an increasing worldwide health problem. The prevalence of asthma is higher in some ethnic minorities and lower in other ethnic groups. Environmental exposures, and psychosocial factors, have been suggested to be main mediators for asthma. Ethnicity related to racial background can influence the differences in asthma through the disease susceptible alleles. Objective: To evaluates environmental and cultural risk factors for asthma among different ethnic groups. Methods: Random sample of 337 Iraqi selected from 5,490 Iraqi residents’ in the Greater Detroit area. Validated questionnaire was used. Chi-square, t-test and logistic regression were used. Results: Results showed a significant difference in the prevalence of asthma among Chaldeans (0.7%) and Arabs (8.7%). However environmental and psychosocial exposures and socioeconomic status were not significantly associated with asthma in Arabs, nor Chaldeans. Conclusion: Even though Arabs and Chaldeans are from the same geographical region, and therefore share similar environmental background history, the asthma prevalence was about 9 times higher in Arabs as compared to Chaldeans. Ethnic background was the only significant risk factor associated with asthma. Genetic differences could explain the high susceptibility to asthma in Arab compared to Chaldean. .